Global Professional Identity in Deterretorialized Spaces: A Case Study of a Critical Dialogue Between Expert and Novice Nonnative English Speaker Teachers (2015)
This study analyzes the online, peer-peer dialogue between two groups of nonnative English-speaking teachers who are attending graduate programs in Colombia and the United States. Framed by the theoretical concepts of critical pedagogy and global professional identity, a qualitative analysis of the data shows that their expert vs. novice roles played a significant part in shaping their positions on the four themes that they discussed: the role of English language teaching in the global world, institutional constraints on teachers, whose culture to teach, and linguistic diversity in the classroom. This study highlights the responsibility of teacher education programs to cultivate healthy nonnative English speaker teachers’ professional identities given the global complexities that continue to unfold around these teachers.En este estudio se analiza el diálogo en línea entre profesores de inglés no nativos, estudiantes de maestría en Colombia y Estados Unidos. El estudio se sustentó en pedagogía crítica e identidad profesional global. El análisis de los datos muestra que los roles experto/novato jugaron un papel relevante en las posiciones que los participantes asumieron con relación a cuatro temas: el papel de la enseñanza del inglés en el mundo global, las limitaciones institucionales sobre los docentes, qué cultura enseñar, y la diversidad lingüística en el salón. Este estudio señala la responsabilidad de los programas de formación docente en promover un desarrollo saludable de la identidad profesional de los profesores no hablantes nativos, dadas las complejidades globales a las que se enfrentan.